One of the Important Elements of the Diet is the Importance of Vitamins (Progress Annals: Journal of Progressive Research, 2024)
Vitamins are low-molecular organic compounds with high activity in small doses. Vitamins can be partially synthesized in the human body, but it is necessary to clarify the question of whether the endogenous synthesis of vitamins D, K, B12 can fully satisfy the body's need for these vitamins. The main part of these vitamins is contained in food products and is absorbed by the body through food (table 2.3.1). The amount of vitamins in food products and their nature are different. For example, fat-soluble vitamin A is readily consumed by the body through milk, dairy products, eggs, butter, and liver. To meet the body's need for vitamin A (1000 mg), water-soluble provitamin A, i.e. carotene, is of great importance. Carotene is found in large amounts in red carrots, bell peppers, and pumpkin products. Vitamin A is synthesized from carotene in the intestine and liver